Non-Primary Home Buyers, Shadow Banking, and the US Housing Market - Alter, Adrian (IMF Working Papers; Working Paper, 2020)
This paper studies the US housing market using a proprietary and comprehensive dataset covering nearly 90 million residential transactions over 1998-2018. First, we document the evolution of different types of investment purchases such as those conducted by short-term buyers, out-of-state buyers, and corporate cash investors. Second, we quantify the contributions of non-primary home buyers to the housing cycle. Our findings suggest that the share of short-term investors grew substantially in the run-up to the global financial crisis (GFC), which amplified the boom-bust cycle, while out-of-state buyers propped up prices in some areas during the recession. An instrumental variable approach is employed to establish a causal relationship between housing investors and prices. Finally, we show that the recent rise of shadow bank lending in the residential market is associated with riskier mortgages, and explore its implications for non-primary home buyers and its effects on house prices and rents.